Exploring the corporate codes of ethics of technological companies in India and comparison with the Indian legal framework - Aranha, Lester (2022)
The intended purpose of this paper is to explore the implementation and usage of the code of ethics in technological companies operating in India and understand the influence and connection of the country’s legal system and its framework on companies employing an ethical code while answering the following research question: What effect does the legal framework of corporate governance have on the codes of ethics and conduct of tech companies operating in India? To fulfil the goals and answer the main research question, the author conducted qualitative secondary research with a pre-selected list of companies, collected data, and conducted a text-comparison-analysis with the Indian code of law. It was revealed that only a small percentage of the ethical codes could be linked to existing laws, and it was not sufficient to prove that an influence can be drawn with the code of ethics.